Socio-environmental impacts of the Minha Casa Minha Vida (My House My Life) Category 1 housing developments in the city of Uberaba-MG - Rodrigues, Pamela de Almeida; Soares, Beatriz Ribeiro (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The objective of this study is to find out the socio-environmental damage caused by the implementation of the three Minha Casa Minha Vida - PMCMV (Brazilian Social Housing Program) subdivisions in the city of Uberaba-MG (Brazil), as well as to understand the dynamics of the program in the city, taking into account the urban planning. For this purpose, a comparative analysis will be carried out between the implementation of the developments destined to the first income category (Category 1) and the urban macrozoning, the social interest zones and the urban perimeter. We will also use the ITDP and LabCidades Urban Insertion Assessment working method for PMCMV category 1 developments and McHarg’s (1969) Suitability Analysis work method in the three subdivisions studied. The PMCMV has been widely criticized during its years in force, one of the main criticisms being the prominence of the private market and how this affects the location of developments and access to urbanized land. In order to understand how this protagonism affects the city, its inhabitants and urban planning in Uberaba, we observed that none of the three subdivisions studied performed satisfactorily after applying the research methods. They do not have acceptable access to public transport, urban facilities, commerce and services, and they are located in areas with potential environmental risks, which already have consequences for the city.